Age-related characteristics of the efficacy of different glucocorticosteroids in the therapy of acute lymphoblastic leukemia - Karachunsky, A I; Rumyantseva, Yu V; Lagoiko, S N; Bührer, C; Tallen, G; Aleinikova, O V; Bydanov, O I; Korepanova, N V; Baidun, L V; Nasedkina, T V; Stackelberg, A Von; Novichkova, G A; et al. (Terapevtic̆eskii arhiv, 2015)
To determine predictors for decision-making on a differential approach to choosing glucocorticosteroids (GCS) for children and adolescents with acute lymphoblastic leukemia (ALL). The analysis covered 1064 primary patients aged to 1 to 18 years with ALL who had been registered at the clinics of Russia and Belorussia in April 2002 to November 2006. Before induction therapy, the patients were randomized into a dexamethasone (DEXA) 6 mg/m2 group (n=539) and a methylprednisolone (MePRED) 60 mg/m2 one (n=525). The entire group showed no statistically significant differences in survival rates between the patients receiving DEXA or MePRED. However, an analysis of age groups revealed the benefits of DEXA in children younger than 14 years (the event-free survival (EFS) was 76±2 and 71±2%, respectively (p=0.048); the overall survival (OS) was 81±2 and 77±2%, respectively (p=0.046); therapy-induced mortality was 6.4% (DEXA) andl 1.1% (MePRED) (p=0.01 4); the rate of isolated extramedullary relapses was 1.5% (DEXA) and 4.4% (MePRED) (p=0.009). At the same time, EFS and OS in 14-to-18-year-old adolescents were statistically significantly higher than in those who used MePRED (EFS, 65±6 and 52±6%, respectively (p=0.087); OS, 72±6 and 61±6%, respectively; (p=0.l 7). The findings suggest that it is possible that the choice of a GCS for ALL therapy must be also based on a patient's age. There is a need for further studies of this matter in prospective randomized multicenter trials in children and adolescents.